2022
DOI: 10.1111/cts.13274
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics of oral trazpiroben (TAK‐906) after organic anion transporting polypeptide 1B1/1B3 inhibition: A phase I, randomized study

Abstract: Trazpiroben is a dopamine D 2 /D 3 receptor antagonist under development for the treatment of gastroparesis. This phase I, open-label, randomized, two-way crossover study (NCT04121078) evaluated the effect of single-dose intravenous rifampin, a potent inhibitor of the organic anion transporting polypeptides (OATPs) 1B1 and 1B3, on the pharmacokinetics and safety of trazpiroben in healthy adults. The utility of coproporphyrin (CP) I and CPIII as biomarkers of OATP inhibition was also assessed. Overall, 12 parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Previous in vitro and animal studies demonstrated that trazpiroben selectively antagonizes D 2 /D 3 receptors with limited central nervous system penetrance, and also shows low affinity for the hERG potassium channel 16,17 . With respect to human studies, trazpiroben was well tolerated in phase 1 clinical trials (NCT03237156) and during phase 1 clinical pharmacology studies 18–22 . A phase 2a study (NCT03268941) assessed the safety profile, pharmacokinetics (PK), and pharmacodynamics of trazpiroben in patients with gastroparesis, with pharmacodynamics evaluated by the effect of trazpiroben on prolactin levels and gastric function 23 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous in vitro and animal studies demonstrated that trazpiroben selectively antagonizes D 2 /D 3 receptors with limited central nervous system penetrance, and also shows low affinity for the hERG potassium channel 16,17 . With respect to human studies, trazpiroben was well tolerated in phase 1 clinical trials (NCT03237156) and during phase 1 clinical pharmacology studies 18–22 . A phase 2a study (NCT03268941) assessed the safety profile, pharmacokinetics (PK), and pharmacodynamics of trazpiroben in patients with gastroparesis, with pharmacodynamics evaluated by the effect of trazpiroben on prolactin levels and gastric function 23 .…”
Section: Introductionmentioning
confidence: 99%
“…16,17 With respect to human studies, trazpiroben was well tolerated in phase 1 clinical trials (NCT03237156) and during phase 1 clinical pharmacology studies. [18][19][20][21][22] A phase 2a study (NCT03268941) assessed the safety profile, pharmacokinetics (PK), and pharmacodynamics of trazpiroben in patients with gastroparesis, with pharmacodynamics evaluated by the effect of trazpiroben on prolactin levels and gastric function. 23 This phase 2a study showed significantly improved volume-to-fullness following the nutrient drink test, and improved American Neurogastroenterology and Motility Society Gastroparesis Cardinal Symptom Index-Daily Diary (ANMS GCSI-DD) symptom scores with trazpiroben, further supporting its development to treat gastroparesis.…”
Section: Introductionmentioning
confidence: 99%